Two Cases of Osteomyelitis Due to Group G Streptococcus - Nirmal Joshi; John N Goldman (Canadian Journal of Infectious Diseases)
Two cases of group G streptococcal osteomyelitis in adults are reported, one of the patients being an otherwise healthy individual. Both cases were successfully treated with parenteral aqueous penicillin G. Only one case of group G streptococcal osteomyelitis has been described previously in the literature; this was in an intravenous drug abuser.